2022
DOI: 10.1111/ijfs.15988
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on physical, techno‐functional and antioxidant properties of corn silk powder

Abstract: The aim of the study was to determine the effect of particle size dispersion of corn silk on physical, techno-functional and antioxidant properties. Corn silk (variety: G5417) was processed into size fractions of 750, 425, 300, 212, 150 and 75 μm and were characterised. The average particle size of the soluble fraction was found to be 364.4 d.nm. The particle size distribution of corn silk powder was found to have a substantial impact on different physical parameters. The results showed a significant decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
3
0
2
Order By: Relevance
“…Conversely, the water absorption of PS-45-ANN, PS-55-ANN, PS-45-55-ANN, and PS-55-45-ANN exhibited a substantial increase compared to the original PS, with increments of 106.21%, 95.61%, 186.92%, and 115.35%, respectively. Notably, the trend of water absorption in annealed starch samples was inversely related to oil absorption, consistent with findings from previous studies (Singh, Kaur, Rasane, Kumar, & Nanda, 2023;S. Zhang, et al, 2022).…”
Section: Tablesupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, the water absorption of PS-45-ANN, PS-55-ANN, PS-45-55-ANN, and PS-55-45-ANN exhibited a substantial increase compared to the original PS, with increments of 106.21%, 95.61%, 186.92%, and 115.35%, respectively. Notably, the trend of water absorption in annealed starch samples was inversely related to oil absorption, consistent with findings from previous studies (Singh, Kaur, Rasane, Kumar, & Nanda, 2023;S. Zhang, et al, 2022).…”
Section: Tablesupporting
confidence: 91%
“…Moreover, a previous study has found that small starch granules exhibit higher adsorption capacity due to their larger specific surface area per unit weight (Naguleswaran, Li, Vasanthan, Bressler, & Hoover, 2012). The lower specific surface area (as shown in Table 1) played a favorable role in reducing oil absorption (Singh, et al, 2023;Yu, et al, 2018). This could also explain why PS-45-55-F exhibited the lowest oil content after frying.…”
Section: Tablementioning
confidence: 87%
“…Singh et al. (2023) related the maximum weight percentage for corn silk powder was found at a particle size of 0.212 mm (31.7%), and the lowest was obtained for 0.075 mm (3%).…”
Section: Resultsmentioning
confidence: 99%
“…It can be observed that most of the YMF particles were retained in 40-mesh (0.420 mm) sieve, whereas most of the BPF particles were retained in 60-mesh (0.250 mm) sieves. Singh et al (2023) related the maximum weight percentage for corn silk powder was found at a particle size of 0.212 mm (31.7%), and the lowest was obtained for 0.075 mm (3%).…”
Section: Physicochemical Characteristicsmentioning
confidence: 90%
“…Flavonoidlerce zengin olan mısır püskülünün, antosiyaninler, tanenler, tanen benzeri polifenoller, fenolik asitler ile karotenoidleri içerdiği belirtilmektedir (Hasanudin vd., 2012;Thapphasaraphong vd., 2016;Abudayeh vd., 2022;Singh vd., 2022d). Geleneksel tıpta antidiyabetik ve antihipertansif olarak bilinen mısır püskülü, gut, hiperglisemi, obezite, ödem, romatizma, sarılık, sistit ve diğer üriner enfeksiyonları tedavi etmek amacıyla kullanılırken, yapılan hayvan testleriyle mısır püskülü ekstraktının pıhtılaşma ve kanama bozukluklarında terapötik potansiyeli olduğu belirtilmektedir (Abudayeh vd., 2022;Singh vd., 2022a;2022b). Mısır püskülü yetiştirildiği bölge, mısır çeşidine ve mısırın olgunluğuna bağlı olarak değişmekle birlikte önemli miktarda karbonhidrat, vitaminler, sodyum, magnezyum, potasyum ve kalsiyum gibi mineraller ile, uçucu yağlar, steroid ve alkaloidler içermektedir (Rahman ve Rosli, 2014;Singh vd., 2022a;2022b).…”
Section: Giriş (Introduction)unclassified